Depresión y su influencia en la calidad de vida de un adulto mayor en tiempos de pandemia - Lopez Andrade, Cristian Bladimir (2021)
The consequences of social isolation on the well-being of older adults is a public health problem that has suffered many scourges from the COVID-19 pandemic. This is how the study reveals that isolation generates risks of having symptoms of depression and anxiety. The elderly in Ecuador is considered a vulnerable age of various physical and mental illnesses, so it requires the necessary attention of different entities dedicated to the well-being of the elderly, however, when a pandemic occurred, no one was prepared for this new normal because of which people were forced to isolate themselves, this situation affects the mental health of older adults. The prevalent factors generated for the development of depression were isolation and fear of contracting the disease. The clinical characteristics were difficulty sleeping, sadness, and decreased appetite. Depression is a disease that was found latent in older adults during the time of the pandemic, significantly affecting their quality of life.